Review of Process Industry Accidents Analysis towards Safety System Improvement and Sustainable Process Design - Athar, M. (2019)
Risk assessment is the tool for maintaining perfect safety management systems and aiding sustainable process design, with hazard identification as the critical step. This step can be executed by past accidents analysis (PAA) to achieve the mentioned objectives. Despite of available analyses, the recurring of accidents identifies the shortcomings in PAA and requires a detailed examination as reported in this review. The intensified exploration of accident information will strengthen both the safety management system at existing facilities and process designing in terms of sustainability. Â© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim